2021
DOI: 10.1111/jhn.12947
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of food and nutrient intake in infants aged 6–12 months, following baby‐led or traditional weaning: A cross‐sectional study

Abstract: Background A baby‐led approach to weaning (BLW) encompasses self‐feeding and self‐selecting graspable foods, offering an alternative to traditional weaning (TW). This cross‐sectional study explored adherence to characteristics of BLW and differences in food group exposure and nutrient intake between babies following either TW or BLW. Methods Nutritional data were collected via multiple‐pass 24‐h recall, following parental completion of an online survey. Results Infants were grouped according to age (6–8 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…Median consumption for both groups was under the WHO recommendation of 830 calories from milk and solids for infants of 9–11 months with one‐third of babies in each group consuming over the EAR. Likewise, this converging of energy intakes between BLW and TW infants was also found in the 24‐h recall reported by Pearce and Langley‐Evans 12 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Median consumption for both groups was under the WHO recommendation of 830 calories from milk and solids for infants of 9–11 months with one‐third of babies in each group consuming over the EAR. Likewise, this converging of energy intakes between BLW and TW infants was also found in the 24‐h recall reported by Pearce and Langley‐Evans 12 …”
Section: Discussionsupporting
confidence: 78%
“…Finally, both UK 24‐h recall studies found low levels of iron consumption, with BLW infants consuming lower amounts than TW infants. This was attributed to a lower intake of iron fortified cereal in BLW infants, although it was also noted that lower levels of iron in breastmilk may skew this issue 10,12 . As noted above, amounts may be lower but absorption occurs at a greater level.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that in infants aged 40-52 weeks, the mean intake in both groups was in line with WHO recommendations of 830 calories from milk and solid foods for infants aged 9-11 months. However, a study in a group of infants aged 26-39 weeks showed that the TW group consumed significantly more energy, carbohydrate, and protein, along with key micronutrients such as iron, calcium, and vitamin D. Pearce et al [44] conducted among TW and BLW children at 6-8 months and 9-12 months observed that spoon-fed children (TW) regardless of age were fed more frequently. No differences in nutrient intake were observed among children aged 9-12 months.…”
Section: Discussionmentioning
confidence: 99%
“… 7 reported that 80% of their sample were educated to at least degree level and, although 69% of “traditionally” weaning mothers were breastfeeding at 6 months, 88% were doing so in the baby‐led group. 7 Similarly, Pearce and Langley‐Evans 6 found that baby‐led weaning mothers were more likely (86% baby led vs. 73% traditional weaning) to be breastfeeding beyond 6 months and were better educated than traditionally weaning women. To put this into context, only 75% of women in England and Wales (where these studies were conducted 6 , 7 ) even initiate breastfeeding and only 34% still breastfeed (only 1% exclusively) to 6 months.…”
Section: Baby‐led Weaningmentioning
confidence: 99%
“…7 Similarly, Pearce and Langley-Evans 6 found that baby-led weaning mothers were more likely (86% baby led vs. 73% traditional weaning) to be breastfeeding beyond 6 months and were better educated than traditionally weaning women. To put this into context, only 75% of women in England and Wales (where these studies were conducted 6,7 ) even initiate breastfeeding and only 34% still breastfeed (only 1% exclusively) to 6 months. The clear sample bias issues in the literature make it difficult to dissect out any real effect of baby-led weaning from generally strong maternal health behaviours.…”
Section: Baby-led Weaningmentioning
confidence: 99%